Residual de herbicidas aplicados na cultura do algodoeiro sobre feijão, milho e soja cultivados em sucessão - Gheno, Eliezer Antonio (2013)
Herbicides that exhibit persistence in soil as fomesafen may present problems in crops grown in succession due to the residual effect in the soil. Thus, the goal of this study was to evaluate whether treatments applied pre -emergence and early post containing fomesafen employees in cotton could undermine the culture of beans, corn and soybean grown in succession . Under the conditions that the experiments were conducted , the observed results demonstrated that herbicide applications resulted in carryover effect for some treatments with the experiments conducted in the greenhouse. However, no significant differences in response variables in any treatment that might impair the development of the cultures of bean , corn and soybeans for periods after the application exceeding 239 days were observed . Thus these results corroborate those found in the field , because the carryover effect seeded corn 264 and 257 days was not observed after herbicide application in pre-and early post -emergence, respectively.